Influence of physiotherapy in the treatment of children with autism spectrum disorder - Reis, Drielly Tífany Ferreira; Pereira, Rafaela Rodrigues; da Silva, Rogerio Alves (Seven Editora, 2023)
Introduction: The etiology of the disorder is not yet well defined, what is known is that several factors can predispose the child to have autism, which may be genetic and environmental factors, according to scientific evidence. The TEA has three measurement degrees, classified as mild, moderate and severe. It is important that the autistic child and his family have the support of a multidisciplinary team that instructs them to overcome the diagnosis and the current situation in which they find themselves. Based on the characteristics presented by the autistic individual, there is a need to develop activities that encourage movement patterns, posture, communication, socialization and psychic, for this reason the physical therapy intervention must occur early, promoting improvements in psychomotor development and daily needs.  Objective: Highlight the benefits of physical therapy as a treatment for children with autism spectrum disorder, present with autism spectrum disorder and talk about the family attitude in view of the autism diagnosis.  Methods: This study qualifies for its basic nature, being a bibliographical research with a qualitative approach, through scientific journals of the last 10 years.  Conclusion: When talking about physiotherapy in ASD, it is possible to understand that as the autistic person undergoes these treatments, their difficulties become smaller.  Physiotherapy allows the child to have physical, motor and emotional well-being.] DOI: https://doi.org/10.56238/thebestiimulti2022-004